Green Politics in the Political Agenda and Village Development Policies in Batu City - Sihidi, Iradhad Taqwa; Romadhan, Ach. Apriyanto; Kamil, Muhammad; Febriana, Naila Noor (Journal of Ecohumanism, 2024)
Village head elections (Pilkades) and village development policies are visual windows to see how green politics is implemented. Examining the implementation of Pilkades in three villages in Batu City and 2 years of leadership of the elected village head, this research aims to see the perspective of green politics, whether it is one of the main political agendas for candidates who are competing and policies by elected candidates during their leadership. The three villages were chosen because they have severe environmental damage problems. The research method applied in this study is qualitative and focused on content analysis of text data, both primary data, including observation data, interviews, and FGDs, and secondary data, including candidates’ Vision-Mission, reports, news, and village government policies related to environmental protection. The results showed that only in Bulukerto and Sumber Brantas did the village head candidates specifically have a vision of environmental conservation, followed by concrete policies during their two years at the helm. Meanwhile, in Pandanrejo, despite facing the impact of environmental damage, the policies implemented are more focused on short-term economic development and have not systematically integrated nature conservation. Furthermore, the results of this study also show that the need for more awareness of the importance of sustainable conservation policies in Pandanrejo is closely related to the community’s view that prioritizes economic and infrastructure issues.